2018
DOI: 10.1007/s12016-017-8661-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex in Respiratory and Skin Allergies

Abstract: A bulk of literature demonstrated that respiratory allergy, and especially asthma, is prevalent in males during childhood, while it becomes more frequent in females from adolescence, i.e., after menarche, to adulthood. The mechanisms underlying the difference between females and males are the effects on the immune response of female hormones and in particular the modulation of inflammatory response by estrogens, as well as the result of the activity of various cells, such as dendritic cells, innate lymphoid ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 65 publications
1
46
2
Order By: Relevance
“…This is, however, inconsistent with our findings of increased prevalence of PCM in men. Notably, the sex distribution trend observed in AD is reversed in individuals over 65 years of age, with more elderly males affected than women . We therefore speculate that similar mechanisms may account for the high prevalence of PCM in males, a disease that also is common in the elderly.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…This is, however, inconsistent with our findings of increased prevalence of PCM in men. Notably, the sex distribution trend observed in AD is reversed in individuals over 65 years of age, with more elderly males affected than women . We therefore speculate that similar mechanisms may account for the high prevalence of PCM in males, a disease that also is common in the elderly.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, we found that males were more frequently affected by PCM than females (Table ). The modulation of immune responses by estrogen, a female hormone, has been well documented . Estrogen enhances type 2 responses and promotes increased production of Th2 cytokines, including IL‐4, IL‐5 and IL‐13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The answers as to why men and women are differently vulnerable to MC-associated diseases are given by their different hormonal state, distinct histamine receptor expression, 101 and gender-dependent number and activity of MCs themselves. 108,109 It has been shown that MCs are receptive for hormonal stimuli, as they express estrogen and progesterone receptors.…”
Section: Ma S T Cell D Is E a S E S-g Ender And De Velopmental Pha mentioning
confidence: 99%